(3MGTjI GdSjO GdTQja Ydi cJGH GdeUHGMs - (3fGUQ Hf YHO GdSjO CHj GdecGQe GHf Ydj, CHh GdaJM, HQgGf GdOjf GdNhGQRej GdeWQRj , J (B610 (3g`s
(3ChdgG (B:s
(3bGd GdeUfa QMeI (B( (3Gddg (B) (3Ydjg (B: (3CeG HYO MeOGddg (B" (3CeG (B" (3cdeI eJVefI deYfi GdTQW , bjd deG ENJdahG ai (B" (3EeG (B" (3abGd HYVge Efg GSe hbGd HYVge Efg MQa s
(3BNQgG (B:s
(3jYfi EPG jcf GdHMK ef LgI GdYGedjI jdRe KHhJ GdNGeS HGdESJbQGA ai CLRGA GddHGH hCHhGHg dG HGdaYd dCf GdaYd jLhR Cf jchf CTjGA CNQi ZjQ GdNGeS s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B348 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B71 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B488s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdfMhs